Decision Making Process in Accelerating Educational Transformation Management - Edy Muslimin; Meti Fatimah; Imam Mujahid (Ta'dib, 2023)
The aim of this research is to determine the decision-making process and management of educational transformation at the Mamba'ul 'Ulum Islamic Institute, Surakarta. The research uses a qualitative approach. Data collection through observation, interviews, literature searches and documentation. Data was analyzed using the Miles & Huberman interaction analysis model, namely data collection, data reduction, data display and conclusion drawing. Checking the validity of the data through triangulation of data sources. The research results show that the decision-making process at the Mamba'ul 'Ulum Surakarta Islamic Institute goes through four stages: problem identification, situation analysis, problem formulation and decision. The management of educational transformation is based on the vision of becoming a world class Islamic Institute characterized by Islam rahmatan lil 'alamin producing individuals with strong faith, lots of knowledge and good deeds by 2035. The educational transformation carried out is: First, the leadership style at IIM Surakarta has transformed to become more democratic. Second, the transformation of higher education governance conventional services to digital-based services. Third, financial management is transformed into outputs and outcomes based. Fourth, the learning method is transformed into blended learning. Fifth, the pattern of cooperation that tends to be formal in meeting accreditation demands is transforming into one based on outcomes and the principle of usefulness.